The Malian fertiliser value chain post-subsidy: an analysis of its structure and performance. Issue 2 (17th February 2018) - Theriault, Veronique; Smale, Melinda; Assima, Amidou
ABSTRACT: This article examines the structure of the Malian fertiliser value chain and its performance in the context of the national subsidy programme, drawing on a review of the literature, farm household survey, and interviews with fertiliser suppliers. It finds that participants in the subsidy programme use more fertiliser and have significantly higher yields. The number of wholesalers and retailers has risen, but procurement remains concentrated. Poor fertiliser quality is a recurrent problem. The high cost of the programme raises questions regarding its sustainability. Mixed performance reflects the need for better monitoring and evaluation, and transparency in the programme.